2009
DOI: 10.1210/jc.2008-1582
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characterization of a Cohort of 161 Unrelated Women with Nonclassical Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency and 330 Family Members

Abstract: The study of family members underlines the variable expression of NC-CAH even within a family, suggesting that modifier factors may modulate phenotype expression. Post-ACTH 21dF cannot reliably detect heterozygous subjects. Considering the high frequency of heterozygotes in the general population, it is essential to genotype the partner(s) of the patients with one severe mutation to offer genetic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
5
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(182 citation statements)
references
References 37 publications
16
152
5
9
Order By: Relevance
“…Basal and ACTH-stimulated 17OHP levels were significantly higher in NC genotype A/C than C/C. These findings are in accordance with other series that included a significant number of NC patients (2,20,40).…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
“…Basal and ACTH-stimulated 17OHP levels were significantly higher in NC genotype A/C than C/C. These findings are in accordance with other series that included a significant number of NC patients (2,20,40).…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
“…A study of the phenotype/genotype relationship in 330 family members revealed 9 symptomatic affected individuals, 42 clinically asymptomatic affected individuals, 242 heterozygotic carriers, and 37 unaffected individuals [51]. As found in this study, affected males are generally asymptomatic and usually identified following the diagnosis of a female family member.…”
Section: Clinical Featuressupporting
confidence: 69%
“…In a multicenter study, the most common symptoms among adolescent and adult women were hirsutism (59%), oligomenorrhea (54%), and acne (33%) [50]. Presenting symptoms in 161 women with NCAH were hirsutism (78%), menstrual dysfunction (54.7%), and decreased fertility (12%) [51].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…An 8 AM value .200 ng/dL (6.0 nmol/L) is suggestive of NCCAH, although it is also compatible with recent ovulation or tumoral hyperandrogenism. 72 This cutoff displayed 92% to 98% sensitivity in detecting NCCAH 73,74 and 12% to 25% specificity in discriminating it from PCOS. 75,76 Thus, unless the 17-OHP level achieves a diagnostic level (.1000 ng/dL = 30 nmol/L), an adrenocorticotropic hormone test is recommended to confirm the diagnosis of NCCAH.…”
Section: Figurementioning
confidence: 98%